HOMOLOGY MODELING AND MOLECULAR DOCKING ANALYSIS OF HUMAN RAC-ALPHA SERINE/THREONINE PROTEIN KINASE - MALIK MOHAMMED ADIL MUSTUFA,; SHUBHRA CHANDRA,; SAIMA WAJID, (International Journal of Pharma and Bio Sciences, 2014)
RAC-alpha serine/threonine-protein kinase (Akt-1) is an enzyme encoded by AKT1 gene in Homo sapiens. Akt-1 is responsible for regulating many cellular processes. An increase in Akt-1 activity inhibits apoptosis leading to cancer. Bexarotene, a retinoid holds a promise to be used in inhibiting cancers. Hesperidin, a flavanoid, can act as an anticarcinogenic agent.. In the present study three-dimensional structure of Akt-1 was successfully modelled using Swiss Model Workspace and validated by Molprobity, Verify 3D, ERRAT2 and ProSA. Molecular docking analysis by iGEMDOCK showed significant binding between the ligands (bexarotene and hesperidin) and Akt-1. Both ligands may be targeted against Akt-1 and after further in vivo investigations these might be used as drugs in cancer treatment.